2010
DOI: 10.1590/s0080-62342010000400003
|View full text |Cite
|
Sign up to set email alerts
|

The demands of family caregivers of elderly individuals with dementia

Abstract: RESUMO RESUMENLa finalidad de este estudio fue identificar características de los cuidadores de ancianos con demencia, tipos de demanda de cuidados y relacionar la demanda con el estadio de la demencia. Este estudio seccional y observacional fue efectuado en 2004 con 104 ancianos y 90 cuidadores en Ribeirão Preto/SP/Brasil, a través del instrumento OARS y un cuestionario para el cuidador. De los 104 ancianos, 66,3% eran mujeres, la edad media fue de 75,5 años y 86,5% del total tenían cuidadores. Entre los cuid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
37
2
17

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 12 publications
5
37
2
17
Order By: Relevance
“…The study showed that most of the individuals in the studied population (n=70) were women and the average age was 84.3 years old (± 8.2), minimum age was 65 years old and maximum was age was 103 years old, while the average age of women was higher than that of men and higher than the average found in other studies (6,13,14) . In terms of education, most participants were either illiterate or had up to four years of education; men displayed a higher average (4.6; ±4.3) of years of education compared to women (3.1; ±4.2), in agreement with data found in another Brazilian study (15,16) .…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…The study showed that most of the individuals in the studied population (n=70) were women and the average age was 84.3 years old (± 8.2), minimum age was 65 years old and maximum was age was 103 years old, while the average age of women was higher than that of men and higher than the average found in other studies (6,13,14) . In terms of education, most participants were either illiterate or had up to four years of education; men displayed a higher average (4.6; ±4.3) of years of education compared to women (3.1; ±4.2), in agreement with data found in another Brazilian study (15,16) .…”
Section: Discussionmentioning
confidence: 50%
“…The rise of positive and negative feelings, psychological conflicts, distress, fear and insecurity, is common with the progression of the disease (6) . Research addressing caregivers of older adults with cognitive impairment in the community is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Caregivers provided care for more than 10 hours a day 23,33,34 . Just over half of all caregivers provided care full time, with about 40% not receiving support from other people and having no previous training in the activity 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, providing them with interventions that support their caregiving work is necessary. (4)(5)(6)(7)(8)(9) In the Spanish social context, family caregivers are the reference point for persons with dependency; their affection and attention are indispensable in order to ensure the patient's quality of life. However, providing affection requires time and effort.…”
Section: Introductionmentioning
confidence: 99%